Assessing service quality of e-waste recycling: A case study from Putrajaya, Malaysia - Haron, Nazatul Faizah; Othman, Mohd Shahwahid (2016)
The quality of recycling services will reflect the effectiveness of recycling performance further improvements. Putrajaya residents were selected as a study site to evaluate the recycling services and assess the ability of the services provided. Data were collected using a stratified random sampling of the households using the questionnaires that have been prior tested for reliability.The critical incident technique (CIT) was used to identify and analyse the satisfaction and dissatisfaction of recycling services. Five successful service constructs identified were a good feeling, secured environment, facilities and efficiency, educational and peer pressure.The paper highlights the form of recovery strategies undertaken by the authorities as perceived by the households.